2020
DOI: 10.4018/978-1-5225-9746-9.ch004
|View full text |Cite
|
Sign up to set email alerts
|

The Era of Digital Technology in Teaching and Learning in Nigeria Educational Institutions

Abstract: The influence of digital technology in society has made it critical for all students in the 21st century to become literate with the use of digital tools. One way to understand the evolving role of digital technologies in education in Nigeria is to review the literature and see how the use of digital technologies in the classroom are documented. The development and proliferation of the internet have contributed to a revolution in teaching and learning; it has also provided new opportunities for delivering inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The assumptions and motives guiding the adoption of a blended approach in both private and public universities are relatively common. They share common insights into how the use of technology can bring about optimal ways to the development of an educational practice that takes into greater account the difference in lectures instructional approaches and learners learning preference, thereby emphasising earlier findings concerning the potential of blended approach to teaching and learning (Anene, et al, 2014;Aladejana and Olajide, 2016;Adeoye, 2020). What differentiates the two is the sort of challenges they faced (specifically with issues of infrastructure, the number of students, and the orientation of students and lecturers) and the institutional policy directions and implementation strategies in places to minimise those challenges.…”
Section: Education Managersmentioning
confidence: 90%
See 3 more Smart Citations
“…The assumptions and motives guiding the adoption of a blended approach in both private and public universities are relatively common. They share common insights into how the use of technology can bring about optimal ways to the development of an educational practice that takes into greater account the difference in lectures instructional approaches and learners learning preference, thereby emphasising earlier findings concerning the potential of blended approach to teaching and learning (Anene, et al, 2014;Aladejana and Olajide, 2016;Adeoye, 2020). What differentiates the two is the sort of challenges they faced (specifically with issues of infrastructure, the number of students, and the orientation of students and lecturers) and the institutional policy directions and implementation strategies in places to minimise those challenges.…”
Section: Education Managersmentioning
confidence: 90%
“…The Nigeria-centric model can be considered a backwards-forward thinking framework as it borrows from colonial and indigenous educational practices, thereby making it pedagogically inclusive and diverse, or perhaps interconnectedly global and local. Although the educational system has relatively repositioned itself through the development of relevant policies, expansion of higher institutions across each state, and the introduction of private universities, studies have shown that the fundamental issues of education in the country remain unsolved (Usoro, 2016;Adeoye, 2020). These issues relate to quality assurance, governance, lack of funding, systematic corruption, and the consequential effect of privatisation and the monetisation of education.…”
Section: Studies Of Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, many institutions may have one or two content-authoring tools supported by the LMS. These fundamental tools allow institutions to form e-Content solutions that embrace a range of teaching approaches, as well as directing current environments to suit a range of social scenarios, learning capabilities, and gender differences [40,41,42]. Such a method, designed to merge student engagement with a range of teaching styles and methods, was proposed in a 2016 study [32].…”
Section: B E-content Developmentmentioning
confidence: 99%